Cisplatin nephrotoxicity: molecular mechanisms - Hanigan, Marie H. (2003)
Cisplatin is one of the most widely used chemotherapeutic agents for the treatment of several human malignancies. The efficacy of cisplatin is dose dependent, but the significant risk of nephrotoxicity frequently hinders the use of higher doses to maximize its antineoplastic effects. Several advances in our understanding of the biochemical and molecular mechanisms underlying cisplatin nephrotoxicity have recently emerged, and are reviewed in this article. Evidence is presented for distinct mechanisms of cisplatin toxicity in actively dividing tumor cells versus the normally quiescent renal proximal tubular epithelial cells. The unexpected role of gamma-glutamyl transpeptidase in cisplatin nephrotoxicity is elucidated. Recent studies demonstrating the ability of proximal tubular cells to metabolize cisplatin to a nephrotoxin are reviewed. The evidence for apoptosis as a major mechanism underlying cisplatin-induced renal cell injury is presented, along with the data exploring the role of specific intracellular pathways that may mediate the programmed cell death. The information gleaned from this review may provide critical clues to novel therapeutic interventions aimed at minimizing cisplatin-induced nephrotoxicity while enhancing its antineoplastic efficacy.